2021
DOI: 10.3390/medicina57030275
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Nutrient Intake and Human Gut Microbiota in Monozygotic Twins

Abstract: Background and Objectives: The gut microbiota is associated with human health and dietary nutrition. Various studies have been reported in this regard, but it is difficult to clearly analyze human gut microbiota as individual differences are significant. The causes of these individual differences in intestinal microflora are genetic and/or environmental. In this study, we focused on differences between identical twins in Japan to clarify the effects of nutrients consumed on the entire gut microbiome, while exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
6
1
Order By: Relevance
“…Given the association between Lachnospira and vitamin D intake [ 25 ], we compared the plasma 25-hydroxy vitamin D levels between patients with and without POAF. We found that 25-hydroxy vitamin D levels were lower in POAF patients compared to no-POAF patients ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Given the association between Lachnospira and vitamin D intake [ 25 ], we compared the plasma 25-hydroxy vitamin D levels between patients with and without POAF. We found that 25-hydroxy vitamin D levels were lower in POAF patients compared to no-POAF patients ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…In the present experiment, we used a powerful analytical technique (16S) followed by a robust statistical analysis (FDR filtered P -value < 0.05), and found no major differences in the relative abundance of phyla and families in the intestinal microbiome; the variation observed was restricted to certain non-abundant genera (CAG-352, Lachnospiraceae UCG-004, [ Eubacterium ] ventriosum group and Allobaculum ). CAG-352 has been linked to human prostate cancer [ 56 ], and the role of the Lachnospiraceae family is far from clear [ 52 , 57 ]. No mechanistic explanation is therefore available on the variation of these Clostridia ( Firmicutes ) in L. infantum -infected hamsters.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors of some studies show that environmental factors outweigh the genetic factors responsible for the composition of the host microbiota [ 27 ]. In their study, Matsumoto et al showed, excluding genetic factors, that individual dietary components affect certain bacterial species [ 28 ]. Polyphenols, proteins, fats, and dietary fiber are essential components of the metabolic pathways of the intestinal microbiota [ 29 ].…”
Section: Influence Of Fiber On the Intestinal Microbiotamentioning
confidence: 99%